(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to the study of the peculiarities and art of the lyrics of Omon Matjon. The article reveals the poet’s contribution to the development of Uzbek poetry of the twentieth century, the unique aspects of his poetry. Several poems of the poet will be analyzed, focusing on the content of the author’s series of poems "I love you". While studying the poems of the poet "Song", "Love", "Uzbek beauty", "Praise to the woman", "I miss you", "Difficult love", "I love you" , we found that romantic expressions are artistically expressed in the language of love in a unique, national spirit, in a way that does not hurt the human heart, using appropriate metaphors and allegories, adapting the basics of life to interpretations of love.